Perencanaan Struktur Gedung Kantor Dishub Kota Pagar Alam Berbasis Program SAP 2000 - Jenny Suwa Muda; M.Sang Gumilar; Fameira Dhiniati (JURNAL ILMIAH BERING'S, 2017)
Building construction has a structural component of beams, columns, and plates. Realize a building structure that is able to withstand the loads that work on the building, it is necessary to select the right type of structural materials such as steel strutur, concrete structure and composite structure. The goals of research to obtain the dimensions of beams, columns and plates capable of withstanding loads that worked planning building structure. The analysis of the calculation of dimensions of beams, columns and plates using SAP 2000 program applications that are safe or capable of carrying the planned load of columns 1 and 2 floors using WF 350 x 350 x 12 x 19 and for floors 3 and 4 using WF 300 x 300 x 10 x 15 with BJ 37 steel quality. 1, 2, 3 and 4 floor beams use WF 200 x 150 x 9 x 16 with BJ 37 steel, and 1, 2, 3 and 4 floor plates using K300 Concrete with 12 cm thick BJTS steel quality 30 Ø12 distance of 20 cm (two layers).